Unpacking The Pathway from Digital Competency to Employee Performance: The Mediating Role of Employee Engagement in The Public Tax Sector - Awang Firdaos; Yusniar Lubis; Robert Tua Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research seeks to examine the influence of digital competency on employee performance, with employee engagement serving as a mediating variable at the Jakarta Mampang Prapatan Tax Office (KPP Pratama). The research employed a quantitative methodology utilizing Structural Equation Modeling (SEM) with Smart PLS, derived from data collected from 106 employees. The findings indicate that digital competency significantly influences employee engagement, which in turn positively affects employee performance. Digital competency also has an indirect effect on how well employees do their jobs by making them more engaged. These results validate that enhancing employee digital competency must be succeeded by bolstering employee engagement to achieve optimal performance improvement. This research makes an empirical contribution to the literature regarding digital competency and work engagement within the public sector and presents practical implications for enhancing human resource capacity to facilitate the modernization of tax services.